Crowdsourcing, Social Media, and Intercultural Communication About Zika: Use Contextualized Research to Bridge the Digital Divide in Global Health Intervention. (April 2020) - Ding, Huiling
This article presents a case study of the Smarter Crowdsourcing project the International Development Bank and Governance Lab cohosted to cope with the emerging Zika outbreaks in Latin America countries. Using the lenses of intercultural communication methodologies, user-centered design, and global cultural flow, I examine the exclusion of at-risk populations as marginalized end users of the project. I also examine the impacts of this oversight on the effectiveness of the technocratic solutions. I then conclude by discussing the implications this case has for international health intervention, global technical communication, and community-based research.